Dubai’s energy efficiency drive - Rashid, FA; Hasbani, KU (Oxford Institute for Energy Studies, 2015)
The Gulf region has been known traditionally as the centre of the global oil and gas industry, and indeed its production has been supplying international markets reliably for decades. However, the region has increasingly been focusing on the policy debate around the Gulf states’ own energy demand and, in particular, on sustainability and clean energy solutions. Diversifying the region’s energy sources, for instance via several GCC states’ ambitious programmes to harness the Gulf’s abundant solar resources, has been one policy response. The United Arab Emirates is home to one such scheme, where Dubai is working towards the production of 1000 MW at its Sheikh Mohammed bin Rashid Al Maktoum solar park. However, another area – demand side management – has also been emerging; this could be critical in ensuring the Gulf region’s sustainable growth over the years to come. Demand side management, together with the related topic of energy efficiency, offers multiple benefits to the economies of Gulf countries.